2015
DOI: 10.1111/acem.12754
|View full text |Cite
|
Sign up to set email alerts
|

Hand Hygiene Compliance in an Emergency Department: The Effect of Crowding

Abstract: Objectives: Emergency department (ED) crowding results from the need to see high volumes of patients of variable acuity within a limited physical space. ED crowding has been associated with poor patient outcomes and increased mortality. The authors evaluated whether ED crowding is also associated with reduced hand hygiene compliance among health care workers.Methods: A trained observer measured hand hygiene compliance using standardized definitions for 22 months in the 40-bed ED of a 475-bed academic hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(70 citation statements)
references
References 9 publications
5
58
2
5
Order By: Relevance
“…In comparison, much of the current literature has relied upon direct observation to study HH compliance. 14,17-22,32-33 Srigley et al demonstrated that the Hawthorne effect can significantly improve HH compliance when HCWs are under direct observation; therefore, true compliance is likely lower than what has previously been reported. In addition, none of these studies have examined compliance with the WHO ‘My 5 Moments’ during initial trauma evaluation and resuscitation when barriers to compliance are likely greatest.…”
Section: Discussionmentioning
confidence: 96%
“…In comparison, much of the current literature has relied upon direct observation to study HH compliance. 14,17-22,32-33 Srigley et al demonstrated that the Hawthorne effect can significantly improve HH compliance when HCWs are under direct observation; therefore, true compliance is likely lower than what has previously been reported. In addition, none of these studies have examined compliance with the WHO ‘My 5 Moments’ during initial trauma evaluation and resuscitation when barriers to compliance are likely greatest.…”
Section: Discussionmentioning
confidence: 96%
“…Research has shown variations in the compliance rates with hand hygiene reported by healthcare professionals, with percentages ranging from 8% to 84.5% (5,(7)(8)(9)16,(22)(23)(24) . However, different factors may be related to low compliance (4,25) .…”
Section: Hand Hygiene Compliancementioning
confidence: 99%
“…Among them, the following are highlighted: healthcare services with limited resources; overcrowding, with inadequate or no spatial separation between beds (26) ; physical structure, which includes poorly located sinks (3,22) ; the use of gloves (16) ; ability, attitudes, and motivation (25) ; the importance given by healthcare professionals to the risks of not being in compliance with the recommendations for hand hygiene; and the training received and the time provided for it (27) . Researchers also continue to point to factors related to inadequate flow of patient care due to overcrowding, heavy workloads, stress, activities with high risk of cross-transmission of pathogens, lack of knowledge about protocols for hand hygiene, lack of positive examples by their superiors, bad habits, simple forgetfulness, and skin irritation and drying caused by the successive use of products (1,4,9,15,20) . In the present study, nurses and physiotherapists showed the highest percentage of compliance (66.6%), and resident physicians, the lowest (41.4%).…”
Section: Hand Hygiene Compliancementioning
confidence: 99%
See 1 more Smart Citation
“…Esta é atribuída conforme autores, a carga de trabalho na referida unidade a fatores contribuintes imprevisíveis, tais como demanda de pacientes, necessidade de escuta terapêutica, insuficiência de profissionais, dentre outros. 8 Ainda, em relação à baixa adesão dos profissionais à HM, autores reforçam a sobrecarga de trabalho, irritação da pele devido à frequente lavagem das mãos, uso excessivo de luvas, pias mal localizadas, conhecimento incipiente dos profissionais de saúde sobre as indicações para higienizá-las, esquecimento e falta de informação sobre o impacto da HM nas taxas das IRAS. 9,10 Com base nas considerações, estabeleceu-se para este estudo a questão de pesquisa: Qual é o conhecimento dos profissionais de enfermagem de um hospital privado quanto à higienização das mãos?…”
Section: Introductionunclassified